A7.1 A Genetic Variant in the Region of MMP-9 is Associated with Serum Levels and Progression of Joint Damage in Rheumatoid Arthritis. (25th February 2013) - Rooy, DPC de; Zhernakova, A; Tsonaka, R; Willemze, A; Kurreeman, BAS; Toes, REM; Huizinga, TWJ; Houwing-Duistermaat, JJ; Gregersen, PK; Helm-van Mil, AHM van der
Abstract : Background and Objectives: The severity of joint destruction is highly variable between Rheumatoid Arthritis (RA) patients. We aimed to identify new genetic risk factors by studying genetic susceptibility loci of several auto-immune diseases. Patients and Methods: In phase-1, 646 Dutch RA-patients with yearly X-rays of hands and feet over 7 years follow-up were genotyped for 148, 880 SNPs by Immunochip which contains 186 loci previously associated with autoimmune diseases. Association of SNPs with MAF > 0.01 (130, 841 SNPS) with joint destruction was analysed using a marginal regression model. Correction for multiple testing was done by Bonferroni correction for the number of uncorrelated SNPs (threshold p < 1.1 × 10 –6 ). In phase-2, 686 North American RA-patients with repeated hands X-rays over 15 years follow-up, for which Immunochip genotyping data were also available, were studied. SNPs that were significantly associated in phase-1 were selected and evaluated. All X-rays were scored by Sharp van der Heijde score (ICC 0.91 and 0.98 for phase-1 and 2 respectively). MMP-9 levels were measured in baseline serum by ELISA (Ebioscience) in 120 RA-patients that were selected on the Rs11908352-genotype. Results: In phase-1, 109 SNPs were significantly associated with joint destruction (p < 1.1 × 10 –6 ). Of these, 76 variants were on the HLA region. The 33 non-HLA genetic variants, though several were in high LD, were studied in the North-American RA-patients. Here, after correction for the number of uncorrelated SNPs (threshold p < 0.0036), two variants were associated with the severity of joint destruction: Rs451066 on chromosome 14 (puncorrected = 0.002, MAF = 0.20) and Rs11908352 on chromosome 20 (puncorrected = 0.002, MAF = 0.21). The region of Rs451066 on chromosome 14 has previously been linked to type-1 diabetes susceptibility. Presence of a risk allele was associated with a 3.7% higher rate of joint destruction per year; this equaled 29% over 7-years. Rs11908352 is located at the MMP-9 region on chromosome 20. Patients with a risk allele had a 2.7% higher radiological progression rate per year, which equaled 20% more joint destruction over a 7-years period. Furthermore, the minor genotype was associated with significantly higher levels of MMP-9 compared to the common genotype (p = 0.007). Conclusions: Two new risk loci for progressive joint destruction in RA were identified (Rs451066 and Rs1190852). The risk allele in Rs11908352 also associated with higher serum MMP-9 levels, indicating to a role for MMP-9 in progression of joint destruction in RA. Acknowledgements: RACI study group, Dutch Arthritis Foundation, Netherlands organisation for scientific research.